2015
DOI: 10.5194/bg-12-6463-2015
|View full text |Cite
|
Sign up to set email alerts
|

Representing northern peatland microtopography and hydrology within the Community Land Model

Abstract: Abstract. Predictive understanding of northern peatland hydrology is a necessary precursor to understanding the fate of massive carbon stores in these systems under the influence of present and future climate change. Current models have begun to address microtopographic controls on peatland hydrology, but none have included a prognostic calculation of peatland water table depth for a vegetated wetland, independent of prescribed regional water tables. We introduce here a new configuration of the Community Land … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 68 publications
2
108
0
Order By: Relevance
“…The peatland area fraction derived from the map of Yu et al (2010) cannot represent the local area providing water for fens. (4) For global applications, the effects of micro-relief were not represented in the model, although they have been shown to be an important regulator of the local hydrology cycle (Gong et al, 2012;Shi et al, 2015).…”
Section: Site-specific V Cmax Reduces Errors In Carbon Flux Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peatland area fraction derived from the map of Yu et al (2010) cannot represent the local area providing water for fens. (4) For global applications, the effects of micro-relief were not represented in the model, although they have been shown to be an important regulator of the local hydrology cycle (Gong et al, 2012;Shi et al, 2015).…”
Section: Site-specific V Cmax Reduces Errors In Carbon Flux Simulationsmentioning
confidence: 99%
“…The simulated water table by ORCHIDEE-PEAT depends on water inflows from the surrounding non-peatland areas, and a water-routing analysis on subgrid scales can be included to improve the model performance for water table in the future (Ringeval et al, 2012;Stocker et al, 2014). Other studies have shown that microtopography exerts important influences on hydrological dynamics of peatlands; however, to capture the influence of microtopography on water table, high-resolution microtopographic feature and vegetation information are needed (Gong et al, 2013;Shi et al, 2015). The poor correspondence between simulated and observed energy fluxes was not completely unexpected, since ORCHIDEE-PEAT only calculates one energy budget for the whole grid cell and not for each soil tile/PFT present in the same grid cell.…”
Section: Orchidee-peat Groups Various Peatland Vegetation Into One Plmentioning
confidence: 99%
“…However, to better quantify and reduce uncertainties arising from deficiencies in model process representation, parameters, driver data sets, and initial conditions, there has been significant effort to evaluate and to calibrate LSMs against site-scale ob-servations and experimental manipulations (Baldocchi et al, 2001;De Kauwe et al, 2014;Hanson et al, 2004;Ostle et al, 2009;Raczka et al, 2013;Richardson et al, 2012;Schaefer et al, 2012;Schwalm et al, 2010;Stoy et al, 2013;Williams et al, 2009;Zaehle et al, 2014). Further, model development from these focused site-scale studies, especially in close collaboration with experimentalists, can inform and prioritize new experiments and observations that are specifically designed to advance understanding of critical terrestrial ecosystems and processes (Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CLM has been evaluated against observations from a wide range of sources, and these evaluations have resulted in improved model performance (Bauerle et al, 2012;Bonan et al, 2011Bonan et al, , 2012Koven et al, 2013;Lawrence et al, 2011;Mao et al, 2012aMao et al, , b, 2013Oleson et al, 2008;Randerson et al, 2009;Riley et al, 2011;Shi et al, 2011Shi et al, , 2013Shi et al, , 2015Thornton et al, 2007). Nevertheless, little attention has been paid to CLM's ability to replicate short-term manipulative experiments, which provide an avenue for exploring and validating model response to sudden, large changes in environmental drivers that control physiological and ecological responses (Amthor et al, 2001;Bonan et al, 2013;Shi et al, 2015). Processes operating over short timescales can have long-lived ecosystem consequences through indirect effects; e.g., stomatal conductance varies on timescales of hours or shorter, but indirect effects on site-level water balance through controls on transpiration can extend to annual timescales and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, including microtopographic information in carbon-balance models is often recommended as a means of improving model accuracies [6,[8][9][10][11]. Most commonly, microtopographic data are acquired via terrestrial surveys using real-time kinematic global navigation satellite system (RTK GNSS) equipment, which are capable of centimeter accuracies [12,13].…”
Section: Introductionmentioning
confidence: 99%